2021
DOI: 10.1042/bcj20210219
|View full text |Cite
|
Sign up to set email alerts
|

Identifying SARS-CoV-2 antiviral compounds by screening for small molecule inhibitors of Nsp14 RNA cap methyltransferase

Abstract: The COVID-19 pandemic has presented itself as one of the most critical public health challenges of the century, with SARS-CoV-2 being the third member of the Coronaviridae family to cause a fatal disease in humans. There is currently only one antiviral compound, remdesivir, that can be used for the treatment of COVID-19. To identify additional potential therapeutics, we investigated the enzymatic proteins encoded in the SARS-CoV-2 genome. In this study, we focussed on the viral RNA cap methyltransferases, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…We next used this assay to determine the effect of substrate concentration on initial reaction velocities. We found that, in contrast with all of the other enzymes we have examined in this series of papers [31][32][33][34][35][36], reaction rates did not plateau at higher substrate concentrations but instead continued to increase non-linearly, indicating that nsp15 endoribonuclease behaves as an allosteric enzyme towards the 6 nt U substrate, with a K half of 2140 nM (Figure 3A and Supplementary Figure S2A).…”
Section: Fluorescent Biochemical Kinetic Screen For Sars-cov-2 Nsp15 Inhibitorsmentioning
confidence: 76%
“…We next used this assay to determine the effect of substrate concentration on initial reaction velocities. We found that, in contrast with all of the other enzymes we have examined in this series of papers [31][32][33][34][35][36], reaction rates did not plateau at higher substrate concentrations but instead continued to increase non-linearly, indicating that nsp15 endoribonuclease behaves as an allosteric enzyme towards the 6 nt U substrate, with a K half of 2140 nM (Figure 3A and Supplementary Figure S2A).…”
Section: Fluorescent Biochemical Kinetic Screen For Sars-cov-2 Nsp15 Inhibitorsmentioning
confidence: 76%
“…64 compounds were selected as primary hits. Compounds were then discounted if: (i) the compound also scored as a strong hit in parallel HTSs of other SARS-CoV-2 enzymes (with the exception of sulphated naphthylamine derivatives, see below) [47][48][49][50][51][52]; (ii) the compound was reported or strongly predicted to be a promiscuous inhibitor due to colloidal aggregation (LogP value >3.6 and >85% similarity to a known aggregator) [53,54]; (iii) the compound was reported or predicted to be a nucleic acid intercalator. This analysis resulted in the selection of 18 compounds for further validation experiments (Supplementary Table S2).…”
Section: Chemical Library Screen Design and Resultsmentioning
confidence: 99%
“…Out of these, 46 primary hits were eliminated as they likely represent nonspecific modes of enzymatic inhibition such as colloidal aggregation or interference with the substrate structure. As part of this analysis promiscuous compounds that were identified as hits in other SARS-CoV-2 HTS [46,[48][49][50][51][52] were removed with the exception of five suramin and suramin-like compounds, which were also identified in the SARS-CoV-2 nsp13 helicase HTS (Zeng et al [46]). In vitro validation of the effect of suramin and suramin-like compounds on the activity of SARS-CoV-2 helicase and SARS-CoV-2 RdRp can be found in Zeng et al [46].…”
Section: Chemical Library Screen Design and Resultsmentioning
confidence: 99%
“…Compounds that inhibited viral replication without deleterious effects on uninfected cells were selected as candidate antivirals. The seven papers describing these results are published in this addition of the Biochemical Journal [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…The other activity of Nsp14 is a guanine N7 methyltransferase involved in the capping of viral RNAs. It was shown [2] that many known drugs inhibited this activity: Lomeguatrib, an inhibitor of O6-methyl guanine DNA methyltransferase that enhances the effect of DNA alkylating agents in cancer treatment; Trifluperidol, used in the treatment of psychoses; IF-03882845 a non-steroidal mineralocorticoid antagonist used to treat diabetic nephropathy. While all inhibited viral replication and had synergistic interactions with remdesivir the severe side effects associated with Trifluperidol may limit its use as a single agent.…”
mentioning
confidence: 99%